2020
DOI: 10.1002/chem.201905771
|View full text |Cite
|
Sign up to set email alerts
|

The First Organosilver(III) Fluoride, [PPh4][(CF3)3AgF]

Abstract: Organosilver(III) fluoride complexes have been assigned a key role in different fluorination processes. To the best of our knowledge, however, none of them seem to have been isolated or even detected thus far. Here we report on the successful synthesis of the trifluoromethyl derivative [PPh4][(CF3)3AgF], which has been isolated in high yield. The thermodynamic stability of the Ag−F bond is shown by calculation and demonstrated by multistage mass spectrometry (MSn) under collision‐induced dissociation (CID) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…In the latter case, the terminal F ligand forms loose [Ag]À F•••HC(sp 2 ) hydrogen bonds with the cation, as already pointed out in our previous communication. [14] The experimentally obtained structures of the [(CF 3 ) 3 AgX] À anions (X=F, Cl, Br) are invariably square-planar (Figure 3), as is usually found in d 8 metal complexes. The most relevant geometric parameters are given in Table 1, where they are compared with those corresponding to the all-organometallic [PPh 4 ][(CF 3 ) 3 AgR] compounds (R=CH 3 , [15] CF 3 ).…”
Section: Experimental Ground-state Structuresmentioning
confidence: 76%
See 3 more Smart Citations
“…In the latter case, the terminal F ligand forms loose [Ag]À F•••HC(sp 2 ) hydrogen bonds with the cation, as already pointed out in our previous communication. [14] The experimentally obtained structures of the [(CF 3 ) 3 AgX] À anions (X=F, Cl, Br) are invariably square-planar (Figure 3), as is usually found in d 8 metal complexes. The most relevant geometric parameters are given in Table 1, where they are compared with those corresponding to the all-organometallic [PPh 4 ][(CF 3 ) 3 AgR] compounds (R=CH 3 , [15] CF 3 ).…”
Section: Experimental Ground-state Structuresmentioning
confidence: 76%
“…[16] We have found, however, that the reaction of complex 2 with AgF in MeCN (Scheme 3) affords the fluoro-derivative [PPh 4 ][(CF 3 ) 3 AgF] (1), which is isolated as a white solid in 75 % yield. [14] This is the first organosilver(III) fluoride compound to have been prepared or even detected. Our preliminary assays demonstrated that the terminal F-ligand in compound 1 is reactive, as it readily undergoes solvolysis with H 2 O and with thiols RSH.…”
Section: Synthetic Proceduresmentioning
confidence: 98%
See 2 more Smart Citations
“…[8] Pioneering work by Ritter, Li, Hartwig and Sarpong allowed for the fluorination of distinct skeletons and pointed to the capital role of elusive Ag II F or Ag III F compounds. [9,10] Most astonishing, organosilver(III) species effecting cross-coupling were authenticated by Ribas, [11] Menjón [12] and Shen [13] who accomplished CÀ C and CÀ heteroatom bond formations nurtured by aryl-Ag III catalyst I, [11] or the trifluoromethylation of thiols and arenes enabled by the anions [Ag III (F)(CF 3 ) 3 ] À II [12] and [Ag III (aryl)(CF 3 ) 3 ] À III, [13] respectively (Figure 1A). [14] From another standpoint, the fluorido-complex II is reminiscent of the long-known homoleptic anion [Ag III (CF 3 ) 4 ] À 1 [15] that pertains to the intriguing coinage metalate(III) series [M III -(CF 3 ) 4 ] À .…”
Section: Introductionmentioning
confidence: 99%